COMPARATIVE ASSESSMENT OF HEMODYNAMICS’ CONDITION AT PATIENTS WITH CCI AND THE ATHEROSCLEROSIS WITH INITIAL DISPLAYS OF INSUFFICIENCY OF BRAIN BLOOD CIRCULATION - Korshnyak, V.A.; Nasibullin, B.A.; Korshnyak, T.V. (World of Medicine and Biology, 2012)
Authors investigated rheological properties of blood, regulation of a vascular tone of blood and a condition of a wall of vessels of an eye bottom at patients with closed craniocerebral injury and an atherosclerosis with initial development infringements of brain blood circulation. On the basis of the comparative analysis of results of inspection of patients different nosology’s authors come to conclusion, that, despite of set of similar clinical displays, in a basis of the revealed infringements different mechanisms of damage lay. Virtue of a difference of pathogenesis mechanisms of mutual influence investigated pathologies have no.